(untitled) (Revista Apotheke, 2022)
This article presents data from a dissertation on the Languages ​​of Art and teaching. This study aims to discuss the complexity of the professional performance of Art Teachers in Visual Arts, Dance, Music, Theater and Integrated Arts. Data collection was carried out through the following procedures: questionnaire and document analysis in line with the bibliographic research. The qualitative analysis of the information took place from graphics generated by the Google Forms platform and the Excel software, as well as by word clouds produced by the Jasondavies website. The collection of information showed that the teaching of Art guided by Law No. 13.278/2016 presents a major dilemma. Regarding the mediation of the polyvalence of the languages ​​of Art, the participants mentioned that it is partially possible, even recognizing the mediation of Visual Arts, Dance, Music, Theater and Integrated Arts as a right of learning for their students. The implication of this study was to cover the impasse of the polyvalence of the languages ​​of Art, which presents itself as a demand of Education and not of Educators.